Role of postoperative use of adrenergic drugs in occurrence of atrial fibrillation after cardiac surgery - Salaria, Vikrant (Clin Cardiol, 2006)
Background: Use of adrenergic (inotropic and vasopressor) drugs is common after cardiac surgery. Hypothesis: The study was undertaken to evaluate the role of postoperative adrenergic drug use as a predictor of postoperative atrial fibrillation (AF) after cardiac surgery. Methods: The study population consisted of 199 patients post cardiac surgery. Postoperative adrenergic drug use and the baseline and clinical variables were analyzed as possible predictors of postoperative AF. Results: Of 199 patients, postoperative AF occurred in 59 patients (incidence 30%). The adrenergic drugs were used in 127 (64%) patients. Postoperative AF occurred in 49 of the 127 patients (39%) with and in 10 of the 72 patients (14%) without adrenergic drug use (p < 0.01). By univariate analyses, postoperative adrenergic drug use, age, left ventricular hypertrophy, left atrial size, valve surgery, aortic valve replacement, cross clamp time, bypass time, postoperative ventricular pacing, and hours in intensive care unit were predictors of development of postoperative AF. Atrial pacing was a predictor of freedom from developing AF. By multivariate logistic regression analysis, adrenergic drug use was an independent predictor of postoperative AF (odds ratio [OR] 3.35, 95% confidence interval [CI] 1.38–8.12, p = 0.016). Two other independent predictors were valve surgery (OR 2.88, 95% CI 1.31–6.35, p = 0.002) and age (OR 10.73, 95% CI 10.37–11.10, p = 0.0001). Adrenergic drug use, valve surgery, ventricular pacing, and age were predictors of time duration from surgery to the occurrence of AF. Drugs with predominantly β(1)‐adrenergic receptor affinity were associated with a higher incidence of postoperative AF (dopamine 44%, dobutamine 41% vs. phenylepherine 20%, p = 0.001). Conclusion: Use of adrenergic drugs is an independent predictor of postoperative AF after cardiac surgery.